زواج المرأة الحامل من الزنا وثبوت النسب منها في قانون الأسرة الإسلامية بولاية الاتحادية كوالالمبور : دراسة تحليلية - Siti Hajar Mohd Zaid (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research aims to study the jurisprudence on the legitimacy of the marriage of the pregnant woman from adultery and the establishment of the kinship of the children born out of wedlock from the perspective of Islamic Law and Islamic Family Law of the Federal Territory of Kuala Lumpur. The research attempts to explain the meaning of marriage, its legitimacy, its rules and the purposes of the marriage. The research then explains the meaning of adultery and its legitimacy. The jurisprudence of the marriage of adulteress and the pregnant woman from adultery is discussed in the second chapter. The research addresses the differences of the jurist views in the jurisprudence of the birth of children born out of wedlock and the establishment of its kinship. Firstly, the research explains the meaning of the children born out of wedlock, and the jurisprudence of the establishment of its kinship and their rights in the Islamic Law and The Islamic Family Law of Federal Territory of Kuala Lumpur. The research defines terminologies that reflects the same meaning with the children born out of wedlock. Some selected cases on the subject are discussed and analyzed from two perspectives, Islamic Law and the Law as well as the solutions from the perspective of Islamic Law and Law. The inductive description method is used by tracking the words of the scholars and facilitating the original and contemporary sources of references in books and heritage. The analytical approach has been used to explains the views of the jurists and laws in the differences of the two. The finding in this research is that it is allowed to marry the adulteress and the pregnant woman from adultery with a particular importance to the repentance before the marriage and staying away from the vice. The research concluded that the kinship of children born out of wedlock has not been established either from the perspective of Islamic Law nor from the fatwa in Malaysia. One of the major finding of the research is that the Malaysia community being easy to the crime of adultery while the sentences imposed by the court is affordable to the adulterers. In conclusion, it is important for the legislative to revise the Law in consistent to the Islamic Law.